Designing a Framework towards Sustainability Leadership in a Higher Education Institution: A Case Study of Gulf University, Bahrain - Omar Blibech (Journal of Sustainability Perspectives, 2026)
This research deliberates the design and implementation of a sustainability leadership framework in a higher education institution. Recognizing the critical role HEIs play in fostering sustainable development, the research aims to identify effective leadership initiatives and strategies that promote environmental, social, and economic sustainability on campus. The research is methodologically grounded in a qualitative case study approach, as the data were collected through developed projects and documents’ analysis and designed actions to assess the current state of sustainability initiatives and leadership practices at Gulf University, Bahrain. Based on the findings, a comprehensive framework emphasizing the design process, strategic leadership, stakeholder engagement, capacity building, design decisions, infrastructure settings and integrated governance is subjected. The proposed framework is aimed at examining a range of challenges and opportunities about how institutional leaders and HEIs can embed sustainability into their core missions, fostering a culture of responsible innovation, and enabling measurable progress toward sustainability goals. The case study reflects the results as valuable insights for policymakers, academic leaders, and sustainability practitioners seeking to advance sustainable practices within higher education settings.